2013
DOI: 10.1002/jgra.50433
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic diagnostics of laboratory air plasmas as a benchmark for spectral rotational (gas) temperature determination in TLEs

Abstract: [1] We have studied laboratory low pressure (0.1 mbar Ä p Ä 2 mbar) glow air discharges by optical emission spectroscopy to discuss several spectroscopic techniques that could be implemented by field spectrographs, depending on the available spectral resolution, to experimentally quantify the gas temperature associated to transient luminous events (TLEs) occurring at different altitudes including blue jets, giant blue jets, and sprites. Laboratory air plasmas have been analyzed from the near UV (300 nm) to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…This spectrograph has a mean spectral resolution of 0.24 nm (with a linear dispersion of 0.07 nm/pixel) and covers the wavelength range between 700 nm and 800 nm with 40 ms (25 fps) temporal resolution (Passas, Sánchez, et al, ) (see supporting information for details). GRASSP is in operation for ground‐based systematic imaging and spectroscopic surveys of all sorts of TLEs in Europe since October 2012 when the first GRASSP version (Parra‐Rojas, Passas, et al, ) was deployed in the Calar Alto Astronomical Observatory (CAHA) (3713'23''N 232'45''W) placed 2,168 m above sea level in southeast Spain. GRASSP recorded from Calar Alto Astronomical Observatory many images of distant TLEs (Passas et al, ) and carried out meteor spectroscopy (Passas, Madiedo, & Gordillo‐Vazquez , ).…”
Section: Introductionmentioning
confidence: 99%
“…This spectrograph has a mean spectral resolution of 0.24 nm (with a linear dispersion of 0.07 nm/pixel) and covers the wavelength range between 700 nm and 800 nm with 40 ms (25 fps) temporal resolution (Passas, Sánchez, et al, ) (see supporting information for details). GRASSP is in operation for ground‐based systematic imaging and spectroscopic surveys of all sorts of TLEs in Europe since October 2012 when the first GRASSP version (Parra‐Rojas, Passas, et al, ) was deployed in the Calar Alto Astronomical Observatory (CAHA) (3713'23''N 232'45''W) placed 2,168 m above sea level in southeast Spain. GRASSP recorded from Calar Alto Astronomical Observatory many images of distant TLEs (Passas et al, ) and carried out meteor spectroscopy (Passas, Madiedo, & Gordillo‐Vazquez , ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical impact and optical signatures of TLEs have been widely investigated by several authors (Gordillo‐Vázquez, ; Kuo et al, ; Parra‐Rojas, Luque, & Gordillo‐Vázquez, ; ; Sentman et al, ; Winkler & Notholt, ). There have also been some ground‐, balloon‐, plane‐, and space‐based instrumentation devoted to the study of TLEs, such as the Imager of Sprites and Upper Atmospheric Lightning (ISUAL; Chern et al, ; Hsu et al, ) of the National Space Organization, Taiwan, that was in operation between May 2004 and June 2016, the Global LIghtning and sprite MeasurementS (GLIMS; Adachi et al, ; Sato et al, ) of the Japan Aerospace Exploration Agency between 2012 and 2015, and the GRAnada Sprite Spectrograph and Polarimeter (Gordillo‐Vázquez et al, ; Parra‐Rojas, Passas, et al, ; Passas et al, , ) and the high‐speed ground‐based photometer array known as PIPER (Marshall et al, ), both of them currently in operation. Despite the valuable advance in the knowledge of TLEs in the last decades, there are still several open questions about the inception and evolution of these events or their global chemical influence in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, 1-ms time resolution spectrograph observations were achieved (Stenbaek-Nielse and McHarg 2004). The altitude-resolved spectrum (with a 3-ms temporal resolution and approximately 3-nm spectral resolution, from 640 -820 nm) revealed that the upper vibrational state population of the N 2 1P bands, B 3 Π g , varies with the altitude, which is similar to the laboratory afterglow at low pressure (Kanmae et al 2007(Kanmae et al , 2010Parra-Rojas et al 2013;Stenbaek-Nielsen et al 2013).…”
Section: Introductionmentioning
confidence: 66%